Structure and Features of Sigma-Delta Modulators - Puidokas, V.; Marcinkevicius, A. J. (Elektronika ir Elektrotechnika, 2008)
The article highlights the main advantages of Sigma-Delta (ΣΔ) converters comparing to Nyquist-rate converters. For the sake of comparison there are presented the main technical characteristics of industrial digital-to-analogue converters (DACs), the description of an ΣΔ DAC structure in case of a 1-bit and multibit quantizer, the analytical description of operation of a 1st order modulator as well as presentation of noise shaping. Also, the analysis of clearer noise shaping was given. Some discussion on application of modulators in power DACs accompanied with its won nuances was presented. There were given several variants on how to increase signal-to-noise ratio (through increasing of oversampling ratio, heightening the order, increasing the number of steps and using multibit quantizers), as well as some problems which arise and aren’t solved in powerful ΣΔ DACs. Ill. 10, bibl. 11 (in English; summaries in English, Russian and Lithuanian).